2021
DOI: 10.1177/00048674211009615
|View full text |Cite
|
Sign up to set email alerts
|

Factors that contribute to urban–rural gradients in risk of schizophrenia: Comparing Danish and Western Australian registers

Abstract: Introduction: An association between schizophrenia and urbanicity has long been observed, with studies in many countries, including several from Denmark, reporting that individuals born/raised in densely populated urban settings have an increased risk of developing schizophrenia compared to those born/raised in rural settings. However, these findings have not been replicated in all studies. In particular, a Western Australian study showed a gradient in the opposite direction which disappeared after adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
1
4
0
1
Order By: Relevance
“…Urban birth is not a robust risk factor among Aboriginals in Western Australia. The results were consistent with Danish findings only when the cohort was restricted to nonaboriginal indigenous status [19].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Urban birth is not a robust risk factor among Aboriginals in Western Australia. The results were consistent with Danish findings only when the cohort was restricted to nonaboriginal indigenous status [19].…”
Section: Resultssupporting
confidence: 89%
“…Global studies on urban birth, upbringing, and urbanicity with schizophrenia/psychosis have produced mixed results. Emerging data suggest that urban birth is associated with an increased risk and incidence of schizophrenia [19–21,22 ▪▪ ,23], particularly in the early years of upbringing to 10 years following birth [24]. Some of the studies suggest that the urban birth effect on schizophrenia is mediated by intelligence quotient, as it explained 53% of the total variance [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with research conducted by McGrath (McGrath et al, 2004) that mental patients are most often found in urban areas. Individuals born, living or raised in densely populated urban environments have a greater risk of developing schizophrenia than those in rural areas (Plana-Ripoll et al, 2021). This is because urban areas are densely populated areas, so they have high levels of poverty, risks of violence, and disease outbreaks that can cause stress (Kristiansson et al, 2015).…”
Section: Characteristics Of Origin Of Districts and Regionsmentioning
confidence: 99%
“…For example, exposure to crime and violence is higher in deprived neighborhoods, but the type of crime experienced may differ by gender, with females potentially being more exposed to sexual violence and males to gang and physical violence (Scorgie et al 2017). The role of sociocultural identities in the experience of social stressors could further explain why the relationship between urbanicity, social exclusion, and mental health disorders might be more multidirectional in some societies, for example, those that are less unequal or are more multicultural (Heinz et al 2020, Krabbendam et al 2021, Plana-Ripoll et al 2021.…”
Section: City Living Chronic Stress Processing and Mental Healthmentioning
confidence: 99%